Evidence from Balinese: Subject-Versus Object-Control Varies According to the Identity of the Verb, but not Necessarily the Probability of the Event Described - I Nyoman Aryawibawa; Gede Primahadi Wijaya Rajeg; Ketut Artawa; Ben Ambridge (Universitas Udayana, 2023)
The objective of the present study was to investigate whether interpretation (Subject-vs-Object control) of an understudied type of control sentence (Sarahi wants someonej [PROi/j] to entertain) depends at least in part on which scenario is most probable. In Study 1, 44 Balinese speakers each rated the relative acceptability of the Subject- and Object-control readings of 272 Balinese sentences of this type. In Study 2, 20 Balinese speakers rated the likelihood of scenarios corresponding to the Subject- and Object-control readings of the sentences from Study 1. Counter to our predictions, however, these ratings did not significantly predict the relative acceptability of the Subject- and Object-control readings from Study 1, apparently because of other, uncontrolled differences between the verbs. We conclude that the question of whether the interpretation of control sentences depends on the relative probability of the scenarios remains unanswered; similar studies in other languages would help resolve this issue